CONTINUING PROFESSIONAL DEVELOPMENT OF ACADEMIC STAFF: THEORETICAL APPROACHES AND MODELS - Lynova, Iryna; Bulvinska, Oksana (Continuing Professional Education: Theory and Practice, 2020)
The article pays attention that usage of a definite theory in educational researches that gives distinct and reproducible explanation of professional experience, becomes the basis of the layout of a practical models of educational practices. It is suggested to classify theoretical approaches and concepts to continuing professional development at philosophical, pedagogical and psychological levels. It was proved that generalization of interconnected systematic synergetic, anthropological, axiological, acmeological, andragogical, and personality-based and activity-based approaches substantiate the aim, tasks, content, forms and methods of continuing professional development of academic staff, take into account self-direction and self-control of individual professional development, and at the same time making it possible to coordinate actions of teachers, make all the adjustments on time, to act on the basis of democracy. It was found out that practical models designed according to these approaches make it possible for the teachers to develop their own educational trajectory, to choose concrete forms, types, tendencies and subjects of educational services individually. But still there is unsolved problem of absence of regulated ways and informal education assessment criteria which is defined as individually controlled professional development, self-organized acquisition of professional competences by the teachers which is not documented. That is what limits possibilities of self-education and its importance for modernization of the system of higher education in Ukraine and for improving of professional practices of each teacher. Every institution of higher education was offered to create their own inter-institutional ways of academic workers’ informal education assessment in the system of their professional development.